Effect of organic substrates on seedling production of giant passion fruit (Passiflora quadrangularis L.) - Shahbani, Nur Shahirah (Asian Network for Scientific Information (ANSINET), 2021)
Passiflora quadrangularis L., also known as giant granadilla, received attention from growers in recent years due to its aromatic flowers, unique and excellent fruit flavor. This research aimed to examine the effect of organic manures used for P. quadrangularis seedlings production. Materials and Methods: The experiment was designed in Randomized Complete Block Design (RCBD), with four treatments consisting of three different organic substrates (chicken, goat and rabbit) and control with six replications. The effect of the treatments was measured through weekly observation on the plant height, stem diameter number of leaves, chlorophyll index and growth rate. After the 4th month of seedling establishment, the root length, fresh weight and biomass of the aerial and root parts were determined and statically analyzed using Analysis of variance (ANOVA) with post hoc Tukey’s test. Results: Among the treatments, the substrates with rabbit composite with soil and sand (T2) exhibited significant Dickson’s Quality Index (DQI), improving the original development of P. quadrangularis seedlings as the plant height of 167.25±1.65 cm, stem diameter of 7.79±0.16 mm and leaves accounted to 28.33±1.20. The fresh and dried aerial mass of 90.41±0.67 and 18.70±0.68 g, respectively and the fresh and dried root mass of 8.92±0.28 and 2.41±0.22 g, respectively was enhanced through the treatment. Conclusion: The constitution of organic substrate in rabbit provides better growth and making its use feasible in the production of P. quadrangularis seedlings.